Odpowiedź:
ćwiczenie 4
a) [tex]\sqrt{(\sqrt{3}-2 )^{2} }[/tex][tex]=|\sqrt{3}-2 |[/tex][tex]= -\sqrt{3}+2[/tex]
b) [tex]\sqrt{(4-2\sqrt{3} )^{2} } = |4-2\sqrt{3} |=4-2\sqrt{3}[/tex]
c) [tex]\sqrt{(2\sqrt{3}-3\sqrt{2} )^{2} } = |2\sqrt{3}-3\sqrt{2} |=-2\sqrt{3} +3\sqrt{2}[/tex]
ćwiczenie 1
a) [tex]|2\frac{1}{2} |+|-2\frac{1}{2} |= 2\frac{1}{2} +2\frac{1}{2} =5[/tex]
b) [tex]|7\frac{1}{4} |-|-7\frac{1}{4} |=7\frac{1}{4} -7\frac{1}{4} = 0[/tex]
c) [tex]|-0,5|+|-0,25|-|0,75|=0,5+0,25-0,75=0[/tex]
d) [tex]2|-\frac{3}{4} |-3|\frac{1}{8} |+4|-\frac{5}{16} |=2*\frac{3}{4} -3*\frac{1}{8} +4*\frac{5}{16}=1\frac{2}{4} -\frac{3}{8}+1\frac{4}{16} =1\frac{8}{16} -\frac{6}{16}+1\frac{4}{16} =2\frac{6}{16} =2\frac{3}{8}[/tex]
e) [tex]1+|1-\sqrt{2} |= 1+(-1+\sqrt{2} )=\sqrt{2}[/tex]
f) [tex]\sqrt{3} -|2-\sqrt{3} |=\sqrt{3} -(2-\sqrt{3} )=\sqrt{3} -2+\sqrt{3} =2\sqrt{3} -2[/tex]